Assessment Of Litopenaeus Vannamei Management Practices in Gujarat, India - Brijesh Kumar; Rama Sharma; Arpita Sharma (Journal of Indian Fisheries Association, 2018)
Shrimp farming has been the fastest growing sector of fisheries and has expended, diversified, intensified substantially by becoming technologically advanced over the last few years. Adoption of management practices recommended by Coastal Aquaculture Authority (CA) has not only helped shrimp farmers to maintain its sustainability but also contributed in resolving social and environmental problems in commercial shrimp farming and thus enhanced country's shrimp production. Adoption levels of the listed twenty management practices by CAA have been studied among shrimp farms in the selected district of Gujarat state. A study was conducted in the purposively selected districts of Gujarat, namely, Surat, Valsad Navsari and Bharuch during 2012 to 2015. Primary data was collected from 180 shrimp farmers to assess their level of adoption by using structured interview schedule. Adoption quotient of each of the management practices in% was calculated based on the formula given by Sengupta, (1967) and ranked from highest (1) to lowest (20) for each of the district. Later, rank of these management practices have been categorized; (1] 1-5rank as vary highly adopted, (II] 6-10 rank as highly adopted, (III) 10-15 rank as moderately adopted and (IV) 16-20 as poorly adopted by shrimp farmers of Gujarat state Results of this study indicated that still there is a scope of improvement in adoption level of these management practices. Therefore, if L vanname farmers place genuine efforts towards attaining higher adoption rate, then shrimp industry of the Gujarat state not only achieve higher productivity and production but also become sustainably and environmentally friendly by reducing the risk which will help the shrimp industry to overcome disease outbreak.